Pembentukan Karakter Akhlakul Karimah Siswa melalui Pembelajaran agama di SDN 1 Tamanharjo Desa Tamanharjo, Kec. Singosari Kab. Malang - Fikri, Maulana Muhammad; Husaini, Muhammad Alwi; Amalia, Rizka Putri; Putri, Dewi Maulida Rahmawati; -, Istikomah; Faulani, Addin Silvia; Purwitasari, Ayu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This journal reviews the formation of student character through religious learning. This study uses the observation method with the main instrument of data collection being students as spectators and the school principal as a resource person by observing, asking and listening to obtain research data. The approach used in this study is a qualitative approach where data is analyzed using descriptive methods. Religious education often prioritizes academic success by ignoring moral principles. Judging from the growth of anti-social behavior, such as brawls between students, theft, murder, assault, and other immoral behavior among students, it's no wonder that many students are experiencing a moral crisis. This writing aims to provide knowledge about the importance of forming the character of students, so that they become human beings who have good morals, are religious and of good quality. The integration and interaction of religious and moral education must occur as a result of social growth in reality. Religion-based education can finally form a complete human being through religious lessons, akhlakul karimah students are encouraged to develop positive traits within themselves that can be applied in everyday life.